KESALAHAN GOOGLE TRANSLATE DALAM MENERJEMAHKAN ENGLISH PHRASAL VERBS KE DALAM BAHASA INDONESIA - Feka, Viktorius P.; Ndapa Lawa, Selfiana T. M.; Liunokas, Ofrisna (FKIP Universitas Citra Bangsa, 2024)
Abstract. This research aims to explore and analyze the errors that commonly occur when translating English phrasal verbs into Indonesian using Google Translate (GT). The research method employed is descriptive-qualitative, and data collection was conducted through a documentation study. The study utilizes descriptive analysis, analyzing all data to obtain results and conclusions. The technique involves several steps, including the identification of data that aligns with the research problem, grouping the data based on the type of phrasal verbs, then, discussing and drawing conclusions. The results of the research indicate the weaknesses of GT in translating English phrasal verbs into Indonesian accurately. GT faces difficulties with three types of phrasal verbs: separable, inseparable, and intransitive. In separable phrasal verbs, GT struggles to transfer the intended meaning accurately, often resulting in a literal translation that mismatches the context. For example,